Race, social support, and coping strategies among HIV-positive gay and bisexual men. - Tate, David C; Van Den Berg, Jacob J; Hansen, Nathan B; Kochman, Arlene; Sikkema, Kathleen J (Culture, health & sexuality, 2006)
Few studies have examined the relation between race, social support, and coping, particularly among HIV-infected individuals. We examined the relation of race and social support to coping with HIV infection in a sample of 121 gay and bisexual men (64 African American, 57 White). Compared to White participants, African Americans reported higher use of multiple coping strategies. High levels of perceived social support were related to greater use of positive coping and seeking support; lower levels of social support were related to greater use of self-destructive coping. There were no race-related differences in social support, and no race by social support interactions. Possible explanations for observed cultural differences and coping challenges of African American gay and bisexual men with HIV are discussed.
Keywords: Adaptation, Psychological; Adult; African Americans; Bisexuality; Cultural Characteristics; Cultural Diversity; European Continental Ancestry Group; HIV Infections; Homosexuality, Male; Humans; Interpersonal Relations; Male; New York City; Questionnaires; Self Concept; Social Support; Wisconsin